2012
DOI: 10.1007/s00005-012-0169-y
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer and Immunoproteome: Awakening and Reprogramming the Guardian Angels

Abstract: Prostate cancer is a life-threatening molecular disorder that is undruggable to date because of stumbling blocks in the standardization of therapy. An emerging framework of research is addressing how pathways that are derailed during tumorigenesis are linked to immunological responses, which are instrumental in immunosurveillance of cancer. However, interestingly, cancer cells circumvent such immunosurveillance through development of poorly immunogenic tumor cell variants (immunoselection) and through subversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Therefore, a lower expression of NKG2D ligand 2 on the surface of cancer cells favors their survival by reducing their chance of being recognized by NK cells. Many studies have focused on triggering the cell surface expression of NKG2D ligands on tumor cells as a potential therapeutic strategy for PCa [3032]. Recently, it was reported that the knockdown of IL-6 in castration-resistant PCa cells rendered them more susceptible than control cells to NK cell-mediated cytotoxicity owing to an increased cell surface expression of NKG2D ligands [33].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a lower expression of NKG2D ligand 2 on the surface of cancer cells favors their survival by reducing their chance of being recognized by NK cells. Many studies have focused on triggering the cell surface expression of NKG2D ligands on tumor cells as a potential therapeutic strategy for PCa [3032]. Recently, it was reported that the knockdown of IL-6 in castration-resistant PCa cells rendered them more susceptible than control cells to NK cell-mediated cytotoxicity owing to an increased cell surface expression of NKG2D ligands [33].…”
Section: Discussionmentioning
confidence: 99%
“…This allows for a mechanismand hypothesis-free exploration of potential drug interactions and, furthermore, makes possible the discovery of more complex and nuanced drug-target interactions [42,43]. This also opens the door for novel approaches, such as phage antimicrobials [63], immune system reprogramming [64] and regenerative medicine [65]. Additionally, predictive bioanalytical tools could also make use of vast data sets of biomedical data, enhancing the repurposing of drugs already approved by the FDA for human use.…”
Section: Translating Atomic-level Mechanistic Understanding To Personmentioning
confidence: 99%
“…Taken together, given exploiting NK cells as a therapeutic strategy for prostate cancer, which has shown promising bene ts in preclinical studies [44], our ndings demonstrated pterostilbene-treated prostate cancer cells enhanced their susceptibility to NK cell-mediated cytotoxicity with promoted IFN-γ and 107a, providing additional evidence for improving NK cell-based immunotherapeutic interventions against prostate cancer.…”
Section: Discussionmentioning
confidence: 64%